Water absorption of fine recycled aggregates: effective determination by a method based on electrical conductivity - Sosa, M. E. (2018)
The high absorption of fine recycled aggregates is indicated as the main difference with respect to fine natural aggregates. This property determines the extra amount of water to be added during mixing to avoid a loss in workability when these aggregates are used for making concrete. Although several methods have been proposed for its determination, none of them has been standardized or has achieved full consensus. In this paper, a method for the determination of absorption based on electrical conductivity is applied. The results from this method and other particular methods proposed in the literature for this type of aggregate are analyzed and compared regarding their representativeness. The outcomes of this study show the suitability of the conductivity method for the effective determination of water absorption of fine recycled concrete aggregate, with relatively low variation and incidence of the operator.